Artificial Intelligence Adoption in Smaller Audit Practices - Mohd Syazwan Karim; Nur Farahah Mohd Pauzi; Adriana Shamsudin; Siti Nurulhuda Mamat; Muhammad Mukhlis Abdul Fatah; Khairiah Ahmad; Nurfarahin Roslan (Information Management and Business Review, 2025)
The emergence of new technologies, such as Artificial Intelligence (AI), is anticipated to profoundlyimpact the accounting and auditing sectors. AI is essential for automating repetitive tasks and enhancing auditjudgment. This study seeks to investigate the adoption of AI in small audit firms in Malaysia. A qualitativeresearch design was employed, involving semi-structured interviews with nine audit supervisors from smallaudit firms in Kuala Lumpur, Negeri Sembilan, Pahang, and Melaka. The discussion focuses on two elements:(1) Perceived Usefulness (PU) – emphasizing how AI enhances audit efficiency and accuracy, and (2) PerceivedEase of Use (PEU) – highlighting the ease of adoption and integration of AI tools into existing audit workflows.The findings reveal that AI is perceived as a valuable tool in small audit firms, improving audit quality andworkflow by significantly accelerating the audit process. However, human expertise is still required for certaincomplex tasks and decision-making. Hence, it is crucial to communicate the AI’s capabilities and constraints toprevent users from experiencing undue disappointment. The findings of this study aim to assist regulators andstandard-setters in developing guidelines, principles, and frameworks for AI adoption among audit firms inMalaysia.